FACTORS INFLUENCING FIRST ANTENATAL CARE AMONG PREGNANT MOTHERS DURING THE FIRST TRIMESTER AT KAJJANSI HEALTH CENTRE IV, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - Nakalanzi, Aisha; Namubiru, Rebecca; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2025)
Antenatal care during pregnancy is a measure to reduce the maternal mortality rate. The study aims to determine the factors influencing first antenatal care among pregnant mothers during the first trimester at Kajjansi Health Centre IV, Wakiso district. Methodology A cross-sectional quantitative study design used a simple random sampling technique. Data from the questionnaires was entered into the computer using the Microsoft Excel program. Analysis was done, and data was presented in the form of tables, figures, and statistical texts depicting respondents’ responses in frequencies and percentages. Results Most 5(45%) of the respondents mentioned delay in detecting abnormalities, 12(40%) thought one should start antenatal care, 11(38%) mentioned that distance to the facility hindered them. Majority 21(70%) of the respondents lacked ultrasound machine at the facility, Majority 18(60%) of the respondents spent long time waiting for service, 63% of the respondents were unaware of delayed ANC attendance. 53.3% of respondents reported that their religion restricted access to antenatal services. The study revealed that most respondents (40%) were between 18 and 20 years. Conclusion Level of knowledge and awareness about the risks of delayed ANC attendance, religious beliefs, geographic challenges, Inadequate healthcare infrastructure were the significant factors that influenced the timing of first ANC visit. Recommendations The government should improve access to healthcare services by expanding healthcare infrastructure in rural and underserved areas.